Management of Mandibular Condyle Fractures in Paediatric Patients: a Systematic Review - Ian Jenkyn; Robert Bosley; Claire Jenkyn; Shadi Basyuni; Christopher Fowell (Stilus Optimus, 2023)
Objectives: This systematic review searched three of the most used databases to assess if current evidence suggested a difference between surgical and non-surgical management of mandibular condyle fractures in paediatric patients. Material and Methods: An electronic literature search was conducted of three well known databases - Ovid, PubMed and Web of Science. Studies included were conducted paediatric patients, in humans, written in English and published from January 1st 1996 until April 1st 2022. Data collection was carried out by two independent reviewers. Data collated from studies without high risk of bias was pooled for surgical vs non-surgical management and total tallies of all outcomes presented. Presence or absence of complications was recorded in 4 x 4 tables for each outcome and compared using a Chi-Square test. Results: After duplicate records were removed, 182 records were screened. After exclusion of unsuitable reports, 20 were included in the review. Further analysis showed the included studies had high risk of bias. Given this, comparison of this pooled data showed no significant difference between management methods. Conclusions: Presently it appears conservative management is functionally adequate without risks associated with surgical management, even though incidence of these risks was shown to be low in the studies included in this review.